Fish luring lamp - XU LI; ZHU GUOLI; LI SHAN; CHEN SHUYI; LI QI (2022)
According to the embodiment of the invention, the fish luring lamp comprises a lamp body provided with a light source system with adjustable luminescence; the temperature sensor is used for collecting external temperature to output corresponding sensor signals; and the controller is coupled with the light source system and the temperature sensor and is used for adjusting the light emitting state of the light source system based on the sensor signal. According to the fish luring lamp capable of achieving self-adjustable light emitting based on the underwater environment temperature, the luring requirements of different types of to-be-caught objects are met, power and energy consumption are controllable, and cost is reduced. 本公开实施例中的诱鱼灯具，诱鱼灯具包括：灯体，设有发光可调的光源系统；温度传感器，采集外部温度以输出相应传感器信号；控制器，耦接所述光源系统及温度传感器，用于基于所述传感器信号调节光源系统的发光状态。本公开实施例中可实现基于水下环境温度而自行可调发光的诱鱼灯具，满足不同种类待捕捞对象引诱需求且可控功率能耗，降低成本。